ACADEMIC CHEATING BEHAVIOR: COMPARISON BETWEEN ACCOUNTING AND NONACCOUNTING STUDENTS - Desirianingsih Haryati Parastri; Andreas Vernando (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2021)
Scandals occurred in various parts of the world result in a crisis of the accounting profession credibility. Various previous literatures provide evidence that cheating behavior in the work environment is significantly related to academic cheating behavior during college. This study aims to investigate how accounting students perceive fraudulent behavior and whether there is a difference between academic cheating behavior between accounting and non-accounting students. This research uses a sample of 203 students consisting of 109 accounting students and 94 non-accounting students from three universities in Yogyakarta. Further, t-test and chi-square test are employed to analyze. This study finds that there are differences in perceptions of fraud between accounting students and non-accounting students. Accounting students are more likely to commit academic fraud than students in other fields. In addition, this study also finds that academic cheating behavior is common because all respondents have at least committed 1 of 13 types of fraudulent behavior. Moreover, students perceive the most serious cheating behavior is using cheat sheets that are not permitted during the exam and viewing or copying from others at the time. Meanwhile, the least serious cheating behavior is finding out the questions in the exam before the exam schedule and working together on assignments that should be finished individually.